Exploring the Interplay of Religious Discrimination and Cognitive Distortions: Insights from Faisalabad (Pakistan) (Journal of Asian Development Studies, 2025)
This study explores the intricate relationship between religious discrimination and cognitive distortions, aiming to provide valuable insights into the psychological dynamics within diverse communities. Building upon existing literature, the study hypothesizes a positive correlation between religious discrimination and cognitive distortions, positing religious discrimination as a predictor for cognitive distortions. A sample of 158 participants comprising 79 Muslims and 79 non-Muslims, 50.6% women, were purposively drawn from Faisalabad city. The age range of the participants was 18-45 years, divided into three subcategories. Among the total participants, 55.7% were literate. The study was conducted by using a cross-sectional correlational study. Data was collected by using a purposive sampling technique. The participants responded to the demographic information sheet, the Religious Discrimination Scale (Allen et al., 2018), and the Cognitive Distortion Scale (Shakeel & Ali, 2015). Results indicated significant positive correlations between cognitive distortions and measures of religious discrimination, highlighting the impact of discrimination on mental processes. Furthermore, multiple linear regression analysis demonstrates the predictive power of religious discrimination on cognitive distortions. Comparison between Muslims and Christians revealed differential experiences of discrimination based on religious identity, with non-Muslims reporting higher levels of psychological distress and cognitive distortions. Moreover, illiterate participants also demonstrated a higher level of religious discrimination as compared to literate participants, regardless of their religion. Despite certain limitations, this study offers implications for research, policymaking, clinical practice, community support, and education, emphasizing the importance of addressing religious discrimination and promoting psychological well-being across diverse communities.